2013
DOI: 10.1177/1479164112467545
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in beta-cell function, dietary intake and expression of the metabolic syndrome among UK adults of South Asian, black African-Caribbean and white-European origin at high risk of metabolic syndrome

Abstract: on behalf of the RISCK Study Group Abstract A cross-sectional analysis of ethnic differences in dietary intake, insulin sensitivity and beta-cell function, using the intravenous glucose tolerance test (IVGTT), was conducted on 497 healthy adult participants of the 'Reading, Imperial, Surrey, Cambridge, and Kings' (RISCK) study. Insulin sensitivity (Si) was significantly lower in African-Caribbean (AC) and South Asian (SA) participants [IVGTT-Si; AC: 2.13 vs SA: 2.25 vs white-European (WE): 2.84 (×10 −4 mL µU m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…South Asian individuals had lower insulin sensitivity than white individuals up to 20 years before they were diagnosed with diabetes. This finding supports previous literature showing decreased insulin sensitivity from a young age among South Asians; this decrease appears decades before the manifestation of diabetes [3, 7, 27, 28]. Plausible explanations for the early emergence of decreased insulin sensitivity include abdominal fat distribution and low muscle mass, unhealthy lifestyles, low levels of adiponectin and high levels of proinflammatory cytokines.…”
Section: Discussionsupporting
confidence: 90%
“…South Asian individuals had lower insulin sensitivity than white individuals up to 20 years before they were diagnosed with diabetes. This finding supports previous literature showing decreased insulin sensitivity from a young age among South Asians; this decrease appears decades before the manifestation of diabetes [3, 7, 27, 28]. Plausible explanations for the early emergence of decreased insulin sensitivity include abdominal fat distribution and low muscle mass, unhealthy lifestyles, low levels of adiponectin and high levels of proinflammatory cytokines.…”
Section: Discussionsupporting
confidence: 90%
“…Previous investigations have examined the relationships between FA and markers of IR in older adults, as well as in unhealthy men and women from geographically distinct populations [18,27]; however, we believe that this is the first study to investigate these relationships in a population of healthy young men and women differing in ethnicity but living in the same geographical region. This enabled us to observe ethnic-specific associations between FA and markers of IR while avoiding the recognized confounder of geographical location.…”
Section: Discussionmentioning
confidence: 97%
“…also demonstrated that individuals of South Asian, African-Caribbean and European origins differ significantly in their habitual dietary intake (e.g. total daily energy intake, % fat intake, and % sugar intake) and that these characteristics are associated with differences in basal insulin sensitivity and secretion [18]. Such ethnic-specific differences are likely not explained by a single factor, but rather a myriad of complex gene-environment interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Low fasting TG concentrations have been extensively reported in populations of African ancestry [1, 31, 32] and are proposed to contribute to the protection from coronary artery disease (CAD) that they exhibit [4, 5]. However recent data have demonstrated that this cardio-protection has been lost amongst younger populations [6, 7] and Blacks no longer exhibit lower TGs than Whites [8].…”
Section: Discussionmentioning
confidence: 99%